HUBUNGAN ANTARA ISO 14001, ENVIRONMENTAL PERFORMANCE DAN ENVIRONMENTAL DISCLOSURE TERHADAP ECONOMIC PERFORMANCE - Rezin Andayani (Universitas Slamet Riyadi, 2015)
This research purposed to determine the relationship between ISO 14001, environmental performance and environmental disclosure to economic performance. Environmental performance is measured using the Performance Rating in Environmental Management (PROPER) are disclosed in the annual report and the company's economic performance is measured using the Return On Asset (ROA). Sampling method with purposive sampling to obtain samples of 15 companies listed in Indonesia Stock Exchange 2011-2013. Methods of data analysis in this study is the Spearman rank correlation and contingency coefficient C. The results showed that: 1) ISO 14001 has no significant positive relationship to economic performance (ROA). 2) environmental performance (PROPER) has a significant positive relationship to economic performance (ROA). 3) environmental disclosure has a significant positive relationship to economic performance (ROA).Keywords: ISO 14001, environmental performance, environmental disclosure, economic performance